Development and Validation of Cyberbullying Measurement Instrument: A Mixed Method Approach - Ecep Supriatna; Fattah Hanurawan; Nur Eva; Hetti Rahmawati (UIN Sunan Gunung Djati, 2023)
This research is motivated by the increasing increase in cyber bullying and the negative impacts it causes. This research aims to develop a cyberbullying measurement instrument using a mixed methods approach involving three stages. Theme exploration stage, namely the qualitative stage with open questionnaire data collection techniques to explore themes surrounding Cyberbullying. At this stage the data analysis technique applied is open coding (65 participants). The testing stage is the content validity stage where the instrument is assessed by experts using the Aiken formula. This stage also includes factor analysis with an exploratory factor analysis (EFA) approach which helps identify the factorial structure underlying the instrument, relationships between items, and grouping items based on dimensions (270 participants). Scale validation stage where at this stage confirmatory factor analysis (CFA) was carried out to test and validate the factorial model identified through EFA (789 Participants). Sampling technique uses convenience sampling technique. The results of the research show that based on the CFA test, the cyber bullying scale showed that all items had loading factor values >0.5 and construct reliability >0.7, as well as AVE results >0.5, so that all the items used were forming factors of the latent variable. The items used are valid and reliable items so they can be relied upon as research measuring tools. Reliable Cyberbullying measurement instruments can more precisely identify cyberbullying behavior and thus can assist in a better understanding of this phenomenon, so that prevention and intervention efforts can be targeted more effectively.